THE CORRELATION BETWEEN STUDENTS READING INTEREST AND THEIR ACADEMIC ACHIEVEMETS ( CASE STUDY IN PL DON BOSKO HIGH SCHOOL SEMARANG) - Qorinta Shinta (UNIVERSITAS STEKOM, 2020)
Abstract Reading is one of many ways to understand science. The interest in reading is an inner encouragement to read, however reading interest does not come naturally instead it must be driven. The research is aimed at oxploring whether there is a correlation between reading interest and learning achievements ( test scores of Indonesian Language ) of Students of PL Don Bosko Semarang. The SPSS test result on the correlation between reading interest and scores of Indonesian Language tests showed sig score 0.012 < 0.05, therefore H0 is refuted. It can be concluded that there is a positive correlation between reading interest and and Test score of Indonesia Language.Key words : Reading, Reading Interest, Correlation, Learning Achivements (Test score)